Feto-Maternal Outcome Of Eclamptic Mothers With Posterior Reversible Encephalopathy Syndrome (Pres) At A Tertiary Care Hospital (Journal of Pharmaceutical Negative Results, 2023)
Background: Eclampsia is one of the riskiest acute pregnancy issues since it has a high risk of morbidity and death for both the mother and the fetus. In underdeveloped nations, there are 50 to 151 cases of eclampsia for every 10,000 deliveries. When combined with eclampsia, reversible posterior leukoencephalopathy syndrome even makes the patient's situation worse and has a negative impact on both the mother and the fetus.Objective: The present study was aimed to determine the obstetric outcomes for the mother and the newborns in PRES at a Federal Government Polyclinic (Postgraduate Medical Institute) IslamabadStudy design: A cross-sectional studyPlace and Duration: This study was conducted in Federal Government Polyclinic (Postgraduate Medical Institute) Islamabad from December 2021 to December 2022.Methodology: Women presenting with eclampsia having neurological symptoms were included in the study. Computed Tomography (CT) of the brain was performed forthe diagnosis of PRES. Women with known seizure disorders or having neurological disorder due to any cause other than eclampsia were excluded. After being diagnosed with PRES and informed consent maternal and fetal outcomes were recorded. Version 25 of SPSS (Statistical package for social sciences) was used to enter and analyse the data. For categorical variables, frequency and percentages as well as mean and standard deviation were collected.Results: Postpartum presentation of eclampsia was 18(45%), 27(67.5%) were primigravida, 65% belonged to rural type of residence, only 11(27.5%) cases were booked. Headache was the most common symptom among patients (42.5%), followed by visual disturbance (27.5%). More than half of the patients (52.5%) had 1-3 convulsions. CT scan revealed that Parieto-occipital region was involved in 19 (47.5%) of patients. The most common maternal complication was Abruptio placentae 8(20%) followed by HELLP syndrome 7(17.5%). Neonatal outcomes revealed that 37.5% of neonates were low birth weight, 7.5% were stillbirthsand only 55% of neonates had APGAR scores between 7-10.Conclusion: Among patients with PRES, prompt diagnosis and therapy are crucial for survival. Clinical and radiographic features need to be carefully considered. The neonatal outcomes also were poor in the study, therefore, a multidisciplinary management strategy will aid in improving the result.